The influences of sea surface temperatures on the rainfall onset in the west-south region of Aceh - Anggun Arwulan Dani; Yopi Ilhamsyah; Syahrul Purnawan (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2024)
Rainfall variability is influenced by several annual global and regional phenomena including the influence of monsoons, El Nino Southern Oscillation (ENSO), Indian Ocean Dipole (IOD), La Nina, and local climates. Sea surface temperature is one of the elements that affect weather patterns in Indonesia. This is because sea surface temperature plays an important role in the evaporation process, thus affecting cloud formation and subsequently affecting rainfall. The purpose of this study was to obtain information about the effect of sea surface temperatures on the onset in the Southwest Aceh region. The method used in this study is the correlation method between sea surface temperature anomalies (SST) and rainfall. The results of this study show that rainfall in the West-South region of Aceh varies greatly and has an equatorial pattern. The equatorial pattern is characterized by a rainfall type with a bimodal shape or there are two rain peaks during the year, namely around March and October. A positive anomaly in the West-South region of Aceh indicated that the rainfall at that time was higher than normal. Meanwhile, negative anomalies indicate that rainfall in the region is lower than normal conditions. The beginning of the average rainy season that occurs in the Southwest Aceh region starts on the 25th which occurs in September and ends until February. The beginning average rainy season that occurs in the West-South region of Aceh, starts on the 25th basis which occurs in September, and ends until February. The highest onset occurred in the Southwest Aceh area, which was 0,2059, and the beginning of the lowest rainy season or regression occurred in the West Aceh area, which was 0,0122.Keywords:Sea surface temperatureRainfallWest-South AcehCorrelation